2016
DOI: 10.1212/wnl.0000000000002510
|View full text |Cite
|
Sign up to set email alerts
|

Advances in levodopa therapy for Parkinson disease

Abstract: Parkinson disease (PD) is a slowly progressive, incurable, neurodegenerative disorder with progressive motor symptoms that can be managed with treatments. Levodopa is generally recognized as the most effective and widely used treatment for PD. It improves function and quality of life, morbidity, and mortality, and therefore reduces individual and societal costs. Levodopa has a relatively short half-life, however, and is quickly metabolized in the plasma, leading to fluctuations, including wearing-off of effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The younger age of onset, longer disease duration, higher levodopa dose, and longer duration of levodopa therapy are considered major clinical risk factors for LID (Zappia and Quattrone, 2008;Warren et al, 2013;Cilia et al, 2014;Perez-Lloret et al, 2017;Matarazzo et al, 2018;Picconi et al, 2018). Young PD patients had a higher risk of LID than PD patients with old age of onset (Kumar et al, 2005;Dhall and Kreitzman, 2016). We analyzed the effect of iron content of SN on all the above clinical risk factors and found that the QSM value of the whole SN showed high accuracy in discriminating PD with LID and HCs (whole SN, 0.9273; left SN, 0.9066; right SN, 0.91) and PD with LID and without LID (whole SN, 0.7163; left SN, 0.7059; right SN, 0.7024).…”
Section: Discussionmentioning
confidence: 99%
“…The younger age of onset, longer disease duration, higher levodopa dose, and longer duration of levodopa therapy are considered major clinical risk factors for LID (Zappia and Quattrone, 2008;Warren et al, 2013;Cilia et al, 2014;Perez-Lloret et al, 2017;Matarazzo et al, 2018;Picconi et al, 2018). Young PD patients had a higher risk of LID than PD patients with old age of onset (Kumar et al, 2005;Dhall and Kreitzman, 2016). We analyzed the effect of iron content of SN on all the above clinical risk factors and found that the QSM value of the whole SN showed high accuracy in discriminating PD with LID and HCs (whole SN, 0.9273; left SN, 0.9066; right SN, 0.91) and PD with LID and without LID (whole SN, 0.7163; left SN, 0.7059; right SN, 0.7024).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a neurodegenerative disorder with progressive motor symptoms [1]. PD affects approximately 3% of the population over 65 years old [2] and is associated with a severe loss in function of dopaminergic neurons within the substantia nigra pars compacta [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery that dopamine loss is associated with PD, this medication is recognized as the most effective drug for PD treatment [1, 21]. However, long-term use of the medication leads to a levodopa-induced decrease in the efficacy of motor benefits and an increase in the incidence of adverse effects, which can contribute to worsening quality of life [20, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…[23,24,25] These include elevations in liver and kidney function test parameters, such as alkaline phosphatase, serum glutamic-oxaloacetic transaminase/aspartate aminotransferase, serum glutamic-pyruvic transaminase/alanine aminotransferase, and bilirubin levels, and abnormalities in BUN and creatinine levels. [23] Thrombocytopenia has also been reported. Nevertheless, in our study, no abnormality in laboratory data was detected.…”
Section: Discussionmentioning
confidence: 99%